Repair organisations in English as second language classrooms in a Ghanaian Technical University - Bukari, Francis; Asafo-Adjei, Ramos; Klu, Ernest Kwesi (Technium Social Sciences Journal, 2022)
Communication breakdowns usually occur in teaching and learning interactions, necessitating repair. This study investigated the types of conversation repair organisations utilised by both lecturers and students during classroom interaction at the Takoradi Technical University. The study adopted the Conversation Analysis (CA) theory as a framework and methodology. The repair organisations identified in the study included self-initiated self-repair, self-initiated other-repair and other-initiated self-repair. Also, during classroom interaction, lecturers and students use paralinguistic elements such silence, cupping of the ear and smiling to convey their feelings and thoughts. Some implications of the study are that university lecturers should repair in their classroom interactions to make them more aware of communication breakdowns and what to do when there are issues with comprehensibility and intelligibility. Additionally, they have to design courses that will educate students on the application of various types of repair organisations and paralinguistic features in classroom discourse to engender effective communication.